The Lack of Parent Participation in Rural Schools - John P. Dolly; D. Patricia Page (Journal of Research in Rural Education, 1983)
The study attempted to assist low-achieving elementary students in a rural school district by providing free training to parents and increasing the number of classroom volunteers. Students scoring in the bottom quartile of the eTBS were identified and their parents contacted. Few parents completed the training; those who did were positive toward the program. Very few parents were willing to serve as classroom volunteers. Most parents refused to participate because they believed their children did not need remediation. Interview data revealed that parents believed their children were performing adequately in school based on the grades they brought home. Parents also commented that their children were performing at the same level as other children in the neighborhood and didn't appear to be in need of remediation. Based on the information they had, parents refused to believe the data indicating the poor performance of their children on the standardized test.